Social interactions in demand - Andrew Grodner; Thomas J. Kniesner (Institute for the Study of Labor (IZA), 2008)
We examine theoretically demand in a two-good economy where the demand of one good is influenced by either a spillover effect in the form of an externality from other consumers' choices and or a conformity effect representing a need for making similar choices as others. A positive spillover effect increases the demand for the good with interactions, and a conformity effect makes the demand curve pivot around the average market demand to make demand less price sensitive. The collateral implication is that spillover in consumption increases the associated derived demand for labor and conformity in consumption makes the associated derived demand for labor less elastic. Finally, we also demonstrate how the presence of a good with social interactions affects the demand for the good without social interactions and the associated demand for the labor producing the non-interactions good.
urn:nbn:de:101:1-20080828248
Keywords: D11; 330; Consumer demand; social interactions; spillover; conformity; labor demand; Konsumtheorie; Soziale Beziehungen; Konsuminterdependenz; Spillover-Effekt; Arbeitsnachfrage; Elastizität; Theorie